The economical freedom in the Islamic thinking - يحيى محمد علي ساجدة عواد صالح (College of Education for Women, 2019)
The economical Freedom is consider one of the issues that took great deal of attention in the Islamic economy for its importance in achieving the economical development by granting the acquiring freedom for the individuals in gaining and getting the fruits of their efforts of work and studying where the goal of this freedom is put on end for poverties, unemployment and erect the foundation of social justice . As for the curriculum which was suitable for this study, it was flying descriptive curriculum and the comparative curriculum, for searching in this subject and by depending on the related resources . The scientific necessity divided this subject in three inquiries: the first the identification of the economical freedom and its legitimate the second: the economical freedom in the normal and Islamic thinking as for the third: the goals of the disciplined freedom in the Islamic economy We had reached from the study of the subject of the economical freedom in the Islamic thinking the prominent facts. -The freedom in the Islamic economy characterized by that it was disciplined to achieve the goals of chances equality and not distinguishing among people to prevent the abusing of the man to his brother. -Also from the goals of the disciplined economical freedom is gaining variety of ownership to fresh the economy by varying its resources and types.